2015
DOI: 10.1111/all.12760
|View full text |Cite
|
Sign up to set email alerts
|

A randomized DBPC trial to determine the optimal effective and safe dose of a SLIT‐birch pollen extract for the treatment of allergic rhinitis: results of a phase II study

Abstract: To cite this article: Pfaar O, van Twuijver E, Boot JD, Opstelten DJE, Klimek L, van Ree R, Diamant Z, Kuna P, Panzner P. A randomized DBPC trial to determine the optimal effective and safe dose of a SLIT-birch pollen extract for the treatment of allergic rhinitis: results of a phase II study. AbstractBackground: Sublingual immunotherapy (SLIT) is a potential efficacious and safe treatment option for patients with respiratory, IgE-mediated allergic diseases. A combined tolerability, dose-finding study with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
0
37
0
2
Order By: Relevance
“…The differences were statistically significant. This study outcome raises questions about the efficacy of SLIT itself 19. Hence, nonperception of efficacy is strongly supported as a reason for nonadherence with this outcome.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The differences were statistically significant. This study outcome raises questions about the efficacy of SLIT itself 19. Hence, nonperception of efficacy is strongly supported as a reason for nonadherence with this outcome.…”
Section: Discussionmentioning
confidence: 82%
“…One starting point for an explanation, however, could be the lack of standardized SLIT dosages. Pfaar et al19 have just reported in a dose-finding study that the most efficient SLIT dose has not yet been established for birch tree pollen. They found that the higher the dosage of birch allergens, the better the symptom scores and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The body of clinical evidence will increase and lead to more products with documented efficacy and safety. In veterinary medicine, central to the above is answering the question “what is the optimal dose of allergen extract in dogs?” Dose‐dependency of ASIT efficacy has been long‐observed in human trials and recent mouse models . Not only the absolute dose, but also the dosing intervals have measurable effects on efficacy under some circumstances.…”
Section: Review Of Current Approaches To Asit In Dogs: How Well Does mentioning
confidence: 99%
“…Dose-dependency of ASIT efficacy has been longobserved in human trials and recent mouse models. 26,27 Not only the absolute dose, but also the dosing intervals have measurable effects on efficacy under some circumstances. Unfortunately, these effects remain unstudied for ASIT in animals.…”
Section: Review Of Current Approaches To Asit In Dogs: How Well Does mentioning
confidence: 99%
“…Dosedependency of ASIT efficacy has been long-observed in human trials and recent mouse models. 26,27 Not only the absolute dose, but also the dosing intervals have measurable effects on efficacy under some circumstances. Unfortunately, these effects remain unstudied for ASIT in animals.…”
Section: Review Of Current Approaches To Asit In Dogs: How Well Does mentioning
confidence: 99%